PENGARUH UKURAN PERUSAHAAN, FINANCIAL LEVERAGE, NET PROFIT MARGIN DAN STRUKTUR KEPEMILIKAN TERHADAP TINDAKAN PERATAAN LABA PADAPERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEIPERIODE 2011-2014 - Siti Herlina; Zulbahridar '; Hariadi Yasni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aims to determine the effect of Firm Size, Financial Leverage, Net Profit Margin and Ownership Structure towards the Income Smoothing on the Manufacturing Business Listed in Indonesia Stock Exchange Periods of 2011-2014.The population in this research is manufacturing business listed in Indonesia Stock Exchange periods of 2011 – 2014. Selection of the sample using purposive sampling method in which the population of 141 selected according to criteria of a sample of 25 companies selected. The method that used to examine the effect of firm Size, Financial Leverage, Net Profit Margin and Ownership Structure towards the Income Smoothing on the Manufacturing Business Listed in Indonesia Stock Exchange Periods of 2011-2014 is multiple linear regression.The results of this study show that firm size effect on income smoothing to the value thitung3,775>ttable1,985 with significant value of 0,039. Financial leverage effect on the income smoothing to the value thitung3,129>ttable1,985 with significant value of 0,018.Net profit margin effect on the income smoothing to the value thitung3,198>ttable1,985 with significant value 0,034. Ownership Structure effect on the income smoothing to the value thitung2,750>ttable1,985 with significant value 0,045.The result of this research showing that the firm size, financial leverage, net profit margin and ownership structure, influential towards the income smoothing. The great effect inflicted (R2) by the fourth of this variables towards dependent variable is 54, 6%. While, the rest is 45, 4% affected by others variables are not completed in this research.Keywords: Size, Leverage, NPM, Ownership,Income Smoothing.